Association between hemoglobin-to-red cell distribution width ratio and depression in Chinese adults: a population-based cross-sectional study - Xu, Yike; Zhang, Shuwen; Liu, Yang; Zhou, Junteng (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the hemoglobin-to-red blood cell distribution width ratio (HRR) and its association with risk of elevated depressive symptoms in Chinese adults, addressing a gap in evidence for non-older populations and exploring potential effect modifiers.MethodsIn this cross-sectional analysis of 30,427 adults from routine health screenings (July 2020–June 2021), depression was assessed using the Self-Rating Depression Scale. HRR was calculated as hemoglobin (g/dL) divided by red cell distribution width (%). Multivariable logistic regression, restricted cubic splines (RCS), sensitivity analyses with alternative depression definitions, E-value analysis, and ROC curve comparisons with the RDW-to-albumin ratio (RAR) were conducted, adjusted for sociodemographic, lifestyle, and clinical confounders.ResultsIn a population of 30,427 adults (46.3% female; mean age 44.9 ± 10.7 years; 56.7% with college education or above) undergoing routine health screenings, a strong inverse graded statistical association was observed between hemoglobin-to-red cell distribution width ratio (HRR) and elevated depressive symptoms (SDS ≥ 53). Each unit increase in HRR reduced elevated depressive symptoms (SDS ≥ 53) by 39% in fully adjusted models (OR = 0.61, 95% CI: 0.51–0.72, p < 0.0001). After adjusting covariates, compared to the lowest quartile (Q1: HRR ≤ 1.031), participants in Q2 (1.031–1.142), Q3 (1.142–1.25), and Q4 (≥1.25) exhibited 10% (OR = 0.90, 95% CI: 0.84–0.98), 13% (OR = 0.87, 95% CI: 0.80–0.94), and 24% (OR = 0.76, 95% CI: 0.70–0.83,) reductions in elevated depressive symptoms (SDS ≥ 53), respectively (p-trend<0.0001). RCS confirmed a linear association without threshold effects. Age modified the relationship (p-interaction = 0.004), with stronger protection in adults ≥45 years (OR = 0.40, 95% CI: 0.32–0.51) than younger individuals (OR = 0.64, 95% CI: 0.50–0.82).ConclusionHRR may indicate an independent, linear inverse association with elevated depressive symptoms (SDS ≥ 53) in Chinese adults, with strong effects in older populations. As a cost-effective hematological biomarker, HRR could support scalable elevated depressive symptoms (SDS ≥ 53) stratification and prevention strategies to complement other risk factors for elevated depressive symptoms, particularly in aging groups, and these findings warrant validation in prospective studies.